Assessment of indoor and outdoor air quality in primary schools of Cyprus during the COVID–19 pandemic measures in May–July 2021. Issue 5 (May 2022) - Konstantinou, Corina; Constantinou, Andria; Kleovoulou, Eleni G.; Kyriacou, Alexis; Kakoulli, Christina; Milis, George; Michaelides, Michalis; Makris, Konstantinos C.
Abstract: Combined pollutant effects from indoor and outdoor sources on children's health, while being at school have not been holistically tackled. The aim of the School Temperature and Environmental Pollutants Study (STEPS) was to perform a school population representative assessment of indoor air quality (IAQ) in primary schools of densely and intermediate populated areas of Cyprus (n = 42). The study took place during May–July 2021 when a school-specific COVID-19 protocol was in place. Questionnaire-based characteristics of schools/classrooms were collected along with 24/48-h long IAQ monitoring of air temperature, relative humidity (RH), particulate matter (PM), carbon dioxide (CO2 ) and volatile organic compounds (VOCs), using low-cost sensors. Mixed effect models assessed the IAQ determinants during school hours. Indoor PM, temperature, RH and VOCs increased with progressing school periods in the day, while indoor CO2 decreased. Indoor RH and CO2 were negatively associated with % open windows, while indoor PM2.5 was positively associated. Most of school time (85%), indoor air temperature exceeded the recommended upper limit (27 °C), while a third of indoor PM2.5 (24-h) measurements exceeded 15 μg/m 3 . The interplay of clean indoor air with adequate ventilation and adaptation to heat stress in schools is important and its comprehensive characterization requires holistic methodological approaches and tools. Highlights: A primary school population representative study of indoor air quality was conducted in Cyprus during May-July 2021. Natural ventilation measures, like open windows and doors during class hours, helped in maintaining adequate ventilation. The study took place during the summer period with indoor air temperature being above the recommended value most of school time. A third of the 24-hour indoor PM2.5 measurements exceeded the WHO recommended value. Abstract : Indoor air quality; School; Environmental pollutants; Sensors; Exposome; COVID–19 measures.